PENGARUH KOMPETENSI TERHADAP KINERJA BENDAHARA DESA (ACCOUNTING STUDY PROGRAM, UNIVERSITAS MUHAMMADIYAH BERAU, 2019)
The current conditions of regional government officials and treasurers are still low, especially in terms of regional financial management (Sidik 2002). At the level of accountability for financial administration management, the competence of human resources in the village is a major obstacle (Subroto 2009). The capacity of human resources in the village has been uneven so far (Yuliana 2013). Factors that influence the performance of treasurer are competencies needed in the completion of a job. Competence affects employee performance. An employee who has high competencies such as knowledge, skills, abilities, and attitudes that are in accordance with the position he holds is always compelled to work effectively, efficiently and productively. This happens because the competencies possessed by the employee concerned are increasingly able to carry out the tasks assigned to him. The sample in this study was the treasurer as village fund manager in Pinrang district. Each variable has a further indicator, these indicators become the starting point for compiling the questionnaire instrument. The answer from the instrument is then measured by a Likert scale. The results showed that the performance had a positive effect on the performance of the village treasurer. The positive influence of competency on the performance of the village treasurer shows that the higher the competency, the more it will improve the performance of the village treasurer. Therefore, it is necessary to test other variables not examined in this study, such as compensation, leadership or organizational culture.